Between Time and Monetary Cost: The Dilemma of Choice Among Customers in Purchase Decision-Making at Retail Stores - Udoh, Ini Smart; Usani, Nfawa Erasmus; Joseph, Uduak E.; Ubong, Martins Christopher (Southeast Asian Business Review, 2026)
Essential aspects of consumer behaviour can be encapsulated over time. Conversely, monetary cost is regarded as the total amount of money necessary to acquire a particular assortment of products. These two aspects can be regarded as essential factors influencing a customer's selection of a retail store for their shopping needs. This paper seeks to elucidate the diverse strategies that consumers use to enhance their shopping experiences, particularly by examining the influence of time and monetary costs on their decision to purchase from a retail store. Data were collected from primary sources, and the study area was Uyo Metropolis of Akwa Ibom State. The sample size for the study was 384 respondents who were selected using the purposive sampling technique from retail stores in the study area. Data collected were treated using the descriptive statistics. Based on their mean score, the result revealed that the respondents highly evaluated four items on the survey instrument relating to their time and monetary value consideration when making purchase decisions. These were items on monetary cost (MC3), indicating that customers appreciate discounts a lot and will rather locate shops that can offer them discounts irrespective of the time they spend shopping (mean = 3.0994, SD = 1.44758). Additionally, the item labelled Purchase Decision (Pd3) indicated that time was crucial in making purchase decisions in retail stores, particularly when urgency was a factor (mean = 3.0653, SD = 1.43173). Then (Time=Tm2), time was of the essence when shopping, so customers would rather go to shops within their proximity (Mean=3.0398, SD=1.46900), and (Time=Tm3) on a scale of time and monetary cost, customers were likely to pick time over the cost of shopping (Mean=3.0114, SD=1.43019). It was concluded that a dual consideration often led to a trade-off; for instance, a customer may opt for a more expensive item that promises a faster shopping experience, thereby conserving valuable time that could otherwise be spent seeking alternatives.